Piano playing-associated musculoskeletal symptoms among tertiary education students in China: the role of playing postures, habits, and emotional states - Zhang, Xueying; Li, Dawen (Frontiers in Psychology, 2025)
BackgroundGiven that research on the prevalence of musculoskeletal symptoms and their associated factors among Chinese piano players remains scarce, this study, situated within the local Chinese cultural context, investigates the current status of playing-associated musculoskeletal symptoms (PAMSS) among piano-playing students in tertiary institutions in China.ObjectiveThis study examines the prevalence and characteristics of PAMSS among piano-playing students in Chinese universities, focusing on two contributing factors: playing postures and playing habits. It further explores the relationships between these symptoms and multidimensional emotional states.MethodsA cross-sectional design was employed. The Chinese Musculoskeletal Questionnaire (CMQ) and the Chinese version of the Positive and Negative Affect Schedule–Expanded (PANAS-X) were administered to 106 university piano learners, including both professional and amateur students. Descriptive statistics, between-group comparisons, correlation analyses, and binary logistic regression models were used to: (a) examine the relationships between PAMSS, playing postures, and playing habits; and (b) explore associations between symptoms and emotional states.ResultsAmong Chinese college piano students, the most frequently reported PAMSS occurred in the neck, shoulders, wrists/hands, and back, primarily affecting the upper limbs, with an overall prevalence of approximately 50%. Playing postures (e.g., seat height settings, wrist postures, shoulder abduction) and playing habits (e.g., relaxation after key touch, breathing patterns) were significantly associated with PAMSS. Symptoms were also associated with three negative emotions—hostility, guilt, and sadness—and with surprise, but no significant association was observed with positive emotions. Female players were more likely to report PAMSS than male players, although this difference warrants further investigation to identify potential contributing factors such as anatomical differences or practice intensity.ConclusionTo reduce the occurrence of PAMSS, piano students should adopt proper playing postures, including maintaining a near-neutral wrist position, keeping the shoulders naturally relaxed and dropped, and avoiding excessive shoulder shrugging. Conscious, regular breathing and prompt relaxation after key touch may also help prevent musculoskeletal problems. While this study identified correlations between PAMSS and emotional states, the bidirectional nature of these relationships requires longitudinal research to determine possible causal mechanisms. Limitations include reliance on self-reported data and restricted sample generalizability, both of which require further validation in future studies.